The forgotten role of food cultures - Bourdichon, François; Arias, Emmanuelle; Babuchowski, Andrzej; Bückle, Anne; Bello, Fabio Dal; Dubois, Aurélie; Fontana, Alessandra; Fritz, Duresa; Kemperman, Rober; Laulund, Svend; McAuliffe, Olivia; Miks, Marta Hanna; et al. (My University, 2021)
Fermentation is one of if not the oldest food processing technique, yet it is still an emerging field when it comes to its numerous mechanisms of action and potential applications. The effect of microbial activity on the taste, bioavailability and preservation of the nutrients and the different food matrices has been deciphered by the insights of molecular microbiology. Among those roles of fermentation in the food chain, biopreservation remains the one most debated. Presumably because it has been underestimated for quite a while, and only considered - based on a food safety and technological approach - from the toxicological and chemical perspective. Biopreservation is not considered as a traditional use, where it has been by design - but forgotten - as the initial goal of fermentation. The 'modern' use of biopreservation is also slightly different from the traditional use, due mainly to changes in cooling of food and other ways of preservation, Extending shelf life is considered to be one of the properties of food additives, classifying - from our perspective - biopreservation wrongly and forgetting the role of fermentation and food cultures. The present review will summarize the current approaches of fermentation as a way to preserve and protect the food, considering the different way in which food cultures and this application could help tackle food waste as an additional control measure to ensure the safety of the food.
Keywords: Biopreservation; Fermentation; Food cultures; Food safety; Mechanism of action; Regulation